The Legal Analysis of the Enforcement of an Arbitral Award - Adeuti, Dr. Bosede Remilekun (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The essence of the introduction of Arbitration will be defeated, if the successful party’ s right of arbitral award is not recognized and not enforceable, in a circumstances wherein the unsuccessful party refused to comply with it. The enforcement of arbitral award in Nigeria has a time limitation which must be enforced within six years for an agreement which is not under seal and time starts to run from the date of the original cause of action and not from the date of making of an arbitral award. It is therefore necessary that parties to an agreement follow all the due process of entering into an agreement, to prevent unforeseen and unredeemable circumstances. This article will re-introduce everything about arbitral award, so that parties to an agreement can be more careful in their dealings. In this article, types of award, legal requirements of an award, enforcement of an arbitral award, procedure for the application and for leave, recognition and enforcement will be discussed.